Influence of source of calories on composition and production of milk - A.J. Gallegos; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1994)
Wheat and tallow increased milk production in a complementary fashion when added to a milo-based grain mix.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Concentrate mixes; Tallow; Wheat; Milo; Milk yield